Diffusion tensor imaging of brain white matter in Huntington gene mutation individuals - Roberta Arb Saba; James H. Yared; Thomas M. Doring; Med Phys; Vanderci Borges; Henrique Ballalai Ferraz (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To evaluate the role of the involvement of white matter tracts in huntingtin gene mutation patients as a potential biomarker of the progression of the disease. Methods We evaluated 34 participants (11 symptomatic huntingtin gene mutation, 12 presymptomatic huntingtin gene mutation, and 11 controls). We performed brain magnetic resonance imaging to assess white matter integrity using diffusion tensor imaging, with measurement of fractional anisotropy. Results We observed a significant decrease of fractional anisotropy in the cortical spinal tracts, corona radiate, corpus callosum, external capsule, thalamic radiations, superior and inferior longitudinal fasciculus, and inferior frontal-occipital fasciculus in the Huntington disease group compared to the control and presymptomatic groups. Reduction of fractional anisotropy is indicative of a degenerative process and axonal loss. There was no statistically significant difference between the presymptomatic and control groups. Conclusion White matter integrity is affected in huntingtin gene mutation symptomatic individuals, but other studies with larger samples are required to assess its usefulness in the progression of the neurodegenerative process.